Impact of comorbid depression on quality of life and disease progression in chronic obstructive pulmonary disease: a correlational analysis - Chen, Yu; Gao, Qianqian; Jia, Hongqin; Qian, Kang; Zhu, Hongbin (Frontiers in Psychiatry, 2025)
IntroductionDepression is a prevalent comorbidity in patients with Chronic Obstructive Pulmonary Disease (COPD), particularly during acute exacerbations (AECOPD), significantly impacting prognosis and quality of life. This study aimed to investigate the risk factors and severity of depression in this population.ObjectiveTo identify risk factors and assess depression severity in patients experiencing Acute Exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD).MethodsAECOPD patients admitted to Chaohu Hospital Affiliated with Anhui Medical University, between October 2023 and February 2025 were included. Participants were divided into four groups using the Patient Health Questionnaire-9 (PHQ-9): mild depression group (n=86), moderate depression group (n=24), severe depression group (n=3), and a control group without depression (n=156). Data collection involved: the first two domains of the World Health Organization Quality of Life questionnaire (WHOQOL-BREF), The Social Impact Scale (SIS) for stigma assessment Clinical data, treatment history, and laboratory test results. A custom-designed questionnaire was utilized to record hospitalization details for intergroup comparisons.ResultsThis study included 269 AECOPD patients, comprising 113 cases in the depression group and 156 controls. Comparative analysis revealed that female patients, those with longer smoking histories, theophyllines users, individuals with greater disease severity, stronger perceived stigma, and poorer quality of life demonstrated higher susceptibility to depression. In depression severity subgroups, 86 cases were classified as mild depression while 27 cases exhibited moderate-to-severe depression. The results demonstrated that gender, glucocorticoid use, daily cigarette consumption, and prolonged hospitalization were significantly associated with aggravated comorbid depression in COPD patients.ConclusionDepressive state in patients with AECOPD is clinically common and associated with factors including gender, smoking history, MMRC grade, disease severity, hospitalization duration, theophyllines use, as well as quality of life and stigma.